The suspendednd Ahaadeeth Which has a lifting ruling and Obligation in the Scientists - Hamad, Ahmed Said; Othman, Fadlan Mohamed; Nazari, Mohamed Aref (Journal of Islamic Sciences, 2018)
The article is to highlight the true picture of the suspended Hadith, which is related to the board of metaphysical or legislative, so that it is difficult to say that this is purely jurisprudence, and therefore ruled that the rule of lifting. And the definition of the language and terminology, and the importance of these conversations and their status in the law, and how the scholars of the Hadith and the owners of Hadith books have taken care of them, but promised those conversations that have suspended the rule of lifting such as raised speeches, this is shown when they are quoted in several places of their books, Under the doors you pict on in their books. And reported the words of scholars in this subject, and their work and reported some recent examples that explain to us the approach of the scholars in dealing with those conversations, and also reported clues or sings through which to rule the suspended Hadith that he has the rule of lifting, and then proved that these conversations are important to take into account And dealing with it in accordance with a sound and proper approach based on the approach that the Hadithies have used in the past and the recent, and God the conciliator.